Penerapan Metode Belajar Tuntas Untuk Meningkatkan Hasil Belajar Mengarang Bahasa Indonesia Siswa Kelas IV SD Negeri 002 Rumbai Pekanbaru - R. Usman (Jurnal Pendidikan, 2011)
The purpose of mastery learning Applied method is to describe of learning hasdone by students to know about the arrange of random sentence to be a good paragraph andwrite based on the chosen word and sentence, based on perfectly spelling in a composition inthe learning curriculum, composition has done arranged based on topic and level of studentsin elementary school 002 Rumbai Pekanbaru the fourth grade to composition in Indonesianclass. Amount of students are thirty two cycles. The processes of this research divided in twocycles. The average of the first student completeness cycle is 66,7 and the secondcompleteness cycle is 76,4% and the result of the first cycle only 24 students 90,63% thesecond cycle only 32 students be 100%.